Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2018
DOI: 10.18653/v1/p18-1116
|View full text |Cite
|
Sign up to set email alerts
|

Forest-Based Neural Machine Translation

Abstract: Tree-based neural machine translation (NMT) approaches, although achieved impressive performance, suffer from a major drawback: they only use the 1best parse tree to direct the translation, which potentially introduces translation mistakes due to parsing errors. For statistical machine translation (SMT), forestbased methods have been proven to be effective for solving this problem, while for NMT this kind of approach has not been attempted. This paper proposes a forest-based NMT method that translates a linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…Although Ma et al (2018) concludes that for RNN-based NMT systems, using packed forests is definitely better than using constituent trees, we found that it is not necessarily true for our syntax-based Transformer. For some configurations, using forests performs worse than using trees.…”
Section: Tree or Forest?contrasting
confidence: 61%
See 4 more Smart Citations
“…Although Ma et al (2018) concludes that for RNN-based NMT systems, using packed forests is definitely better than using constituent trees, we found that it is not necessarily true for our syntax-based Transformer. For some configurations, using forests performs worse than using trees.…”
Section: Tree or Forest?contrasting
confidence: 61%
“…Note that we used absolute positional encoding instead of syntax-based positional encoding, so we can conclude that the improvement on performance was completely from syntax scores. This indicates that scores are important for the syntax-based Transformer, as was the case with the syntax-based NMT based on RNNs as demonstrated in Ma et al (2018).…”
Section: Influence Of Scoresmentioning
confidence: 73%
See 3 more Smart Citations